Association between the kinetics of cytomegalovirus reactivation in terms of the area under the curve of cytomegalovirus antigenemia and non‐relapse mortality after allogeneic hematopoietic stem cell transplantation. Issue 5 (26th August 2021) - Takeshita, Junko; Kimura, Shun‐ichi; Nakasone, Hideki; Kawamura, Shunto; Nakamura, Yuhei; Kawamura, Masakatsu; Yoshino, Nozomu; Misaki, Yukiko; Yoshimura, Kazuki; Matsumi, Shimpei; Gomyo, Ayumi; Tamaki, Masaharu; et al.
Abstract: Background: We assessed the kinetics of cytomegalovirus (CMV) reactivation using the area under the curve (AUC), which simultaneously reflects both the viral load at each time point and the duration of CMV antigenemia (CMV‐AG). Methods: We performed a single‐institute retrospective analysis in patients who received allogeneic hematopoietic stem cell transplantation (HSCT) between 2007 and 2017 and survived more than 100 days after HSCT. The AUC of CMV‐AG (CMV‐AUC) was calculated by a trapezoidal method using the number of CMV‐AG tested by the C10/C11 method after logarithmic transformation, and plotted weekly up to day 100. Results: CMV reactivation was observed in 195 cases and the median CMV‐AUC for CMV‐reactivated patients was 8.7 (range 0.5–30.7). Older age, corticosteroid administration, CMV‐seropositive transplant recipients, HSCT from an unrelated donor, and underlying diseases were independent predictive factors for higher CMV‐AUC. Higher CMV‐AUC was associated with poor overall survival (OS) with borderline significance in a univariate analysis ( p  = .07), but was not significant in a multivariate analysis. Older age, high‐risk disease status, and female gender were identified as significant factors associated with poor OS in this study. On the other hand, CMV‐AUC (hazard ratio: no reactivation reference, low 0.98, high 2.49, p  < .01), older age, HCT‐CI ≥3, and corticosteroid administration were identified as significant factors associated with increased incidence of non‐relapse mortality (NRM). Conclusions: The kinetics of CMV reactivation in terms of CMV‐AUC reflect both the severity and duration of CMV reactivation. High CMV‐AUC was associated with an increased incidence of NRM in survivors over 100 days.